Host adaptation in Phytophthora infestans: a review from a population biology perspective - Andrivon, Didier; Corbière, Roselyne; Lebreton, Lionel; Pilet, Fabian; Montarry, Josselin; Pellé, Roland; Ellissèche, Daniel (Plant Breeding and Seed Science, 2004)
Phytophthora infestans behaves in natural and agricultural ecosystems as a biotrophic pathogen, although it can be cultured on artificial media. Pathogenicity and host adaptation are therefore essential traits to understand its biology and to come up with durable, efficient management of late blight. The present review focuses on adaptation to host species and host cultivars, and to both qualitative and quantitative types of resistance. It also discusses some of the patterns and population mechanisms involved in this adaptation, such as selection, genetic drift and migration. This highlights the need for an in-depth analysis of each local situation to accurately describe and understand the mechanisms responsible for observed population displacements.